A study of non-alcoholic fatty liver disease (NAFLD) in South African patients and analysis of candidate genes in insulin resistance and fatty acid oxidation. - Kruger, F. C. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Medicine. Internal Medicine))--Stellenbosch University, 2008.